KS01.5.A Impact of reduced treatment volumes on pattern of tumor recurrence and radiation dose to normal brain parenchyma in glioblastoma. (5th September 2022) - Minniti, G; Giraffa, M; Capone, L; Raza, G; Russo, I; Navarria, P; Tini, P; Romano, A; Bozzao, A; Paolini, S; Esposito, V
Abstract: Background: to analyze GBM recurrence pattern after standard chemoradiotherapy according to different target volume delineations. We hypothesized that reduced target volume margins may result in similar pattern of failure. Material and Methods: 207 patients with GBM who recurred after standard chemoradiation were evaluated. According to the Advisory Committee for Radiation Oncology Practice (ACROP) committee of the European Organisation for Research and Treatment of Cancer (EORTC) target volume delineation guideline, the clinical target volume (CTV) used for treatment planning consisted of residual tumor and resection cavity plus 2-cm margin. MRI scans showing tumor recurrences were fused with the planning computed tomography (CT), and the patterns of failure were analyzed dosimetrically using dose-volume histograms. The recurrent lesions were defined as in-field, marginal, or distant if >80%, 20-80%, or <20% of the intersecting volume was included in the 95% isodose line. For each patient a theoretical plan consisting of a reduced CTV using 1-cm margin was created and patterns of failure evaluated. Results: The median overall survival and progression-free survival were 15.3 months and 7.8 months, respectively, from the date of surgery. Recurrences were in-field in 180 patients, marginal in 5 patients, and distant in 22 patients. Analysis of O6-methylguanine-DNA-methyltransferase (MGMT) promoter methylation status showed different recurrence patterns of GBMs in patients with MGMT methylated compared with patients with MGMT unmethylated status. Recurrences occurred in-field and distant in 75.6% and 18.6% of methylated patients and in 91.8% and 6% of unmethylated patients, respectively (p=0.0046). Patterns of failure were similar between the different treatment plans. Reduced target volumes were associated with significantly lower doses of 20-50 Gy to normal brain and hippocampi (p=0.0001). Conclusion: Most of patients treated with standard chemioradiotherapy have in-field recurrences; however, an increased risk of distant recurrences occurs in methylated tumors. The use of target delineation using 1-cm CTV margin is associated with smaller volumes of normal brain and hippocampi irradiated to high doses, without significant changes in the pattern of failure. The impact of different target delineation in terms of efficacy and risk of late radiation-induced toxicity should be assessed prospectively.